Predicting the Relationship of Antecedent Variables of Intention to Use: Empirical Analysis on E-Money Application - Iswara, Ganesha Triutomo; Wialdy, Kevin; Sihombing, Sabrina Oktaria (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2019)
This study aims to predict the relationship of perceived usefulness, perceived ease of use, relative superiority, nature of transactions, and substitution to adoptions that affect intention to use of smart phone-based electronic money. The variables in this study are relative advantages, transaction nature, perceived usefulness, and perceived ease of use, substitution and adoption of electronic money. Data collection techniques in this study were conducted using a questionnaire with judgmental sampling method. The size of the respondents is 142 respondents. The data obtained is analyzed using Structural Equation Modeling (SEM). The results show that the six hypotheses are supported. The intention to use electronic money is also influenced by the adoption of electronic money. The adoption of electronic money is a significant predictor of intention to use electronic money. This study also provides limitations and suggestions for further research.